Alternative non-linear demand estimation methods for probability-based seismic assessments. - Jalayer, F. (Earthquake engineering & structural dynamics.)
Alternative non-linear dynamic analysis procedures, using real ground motion records, can be used to make probability-based seismic assessments. These procedures can be used both to obtain parameter estimates for specific probabilistic assessment criteria such as demand and capacity factored design and also to make direct probabilistic performance assessments using numerical methods. Multiple-stripe analysis is a non-linear dynamic analysis method that can be used for performance-based assessments for a wide range of ground motion intensities and multiple performance objectives from onset of damage through global collapse. Alternatively, the amount of analysis effort needed in the performance assessments can be reduced by performing the structural analyses and estimating the main parameters in the region of ground motion intensity levels of interest. In particular, single-stripe and double-stripe analysis can provide local probabilistic demand assessments using minimal number of structural analyses (around 20 to 40). As a case study, the displacement-based seismic performance of an older reinforced concrete frame structure, which is known to have suffered shear failure in its columns during the 1994 Northridge Earthquake, is evaluated.